Cleavage of factor XIII by human neutrophil elastase results in a novel active truncated form of factor XIII A subunit - Bagoly, Zsuzsa; Fazakas, Ferenc; Komáromi, István; Haramura, Gizella; Tóth, Eszter; Muszbek, László (Thrombosis and Haemostasis, 2008)
The first step in the activation of plasma factor XIII (FXIII) is the cleavage of R37-G38 bond in FXIIIA subunit (FXIII-A) by thrombin, which makes the subsequent formation of an active transglutaminase possible. No active truncated form of FXIII-A, other than G38-FXIII-A, has been identified. In contrast to thrombin, which has a preference toward arginine residues, human neutrophil elastase (HNE) cleaves peptide bonds at small side-chain aliphatic amino acids, preferably at valine. As there are several valine residues close to the thrombin cleavage-site, we tested if an active truncated FXIII-A was formed during fragmentation of FXIII by HNE. It was demonstrated by Western blotting and transglutaminase assay that HNE induced a limited cleavage of FXIII-A resulting in the activation of both plasma and cellular FXIII; the maximal transglutaminase activities were 52.5% and 67.4% of thrombin-activated FXIII, respectively. After the relatively rapid activation a much slower inactivation occurred. HNE-activated FXIII cross-linked fibrin γ- and α-chains in the clot formed by batroxobin moojeni. MALDI-TOF analysis of the cleaved fragments and N-terminal Edman degradation of the truncated protein identified V39-N40 as the primary cleavagesite and N40-FXIII-A as the active form. No primary cleavage occurred at V34, V35, V47, V50 residues. FXIII-A V34L polymorphism, which increases the rate of FXIII-A cleavage by thrombin, was without effect on FXIII activation by HNE. Molecular modeling located the primary HNE cleavage-site in the middle of the flexible and accessible Q32-L45 loop and showed that other neighboring valine residues were in less favorable position.
Keywords: Factor XIII; transglutaminase; elastase; factor XIII-A V34L polymorphism